2010
DOI: 10.1371/journal.pone.0012811
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Blisters in Lipid Bilayers: Implications for Lipid Droplet Biogenesis and the Mobile Lipid Signal in Cancer Cell Membranes

Abstract: Triglycerides have a limited solubility, around 3%, in phosphatidylcholine lipid bilayers. Using millisecond-scale course grained molecular dynamics simulations, we show that the model lipid bilayer can accommodate a higher concentration of triolein (TO) than earlier anticipated, by sequestering triolein molecules to the bilayer center in the form of a disordered, isotropic, mobile neutral lipid aggregate, at least 17 nm in diameter, which forms spontaneously, and remains stable on at least the microsecond tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
162
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(179 citation statements)
references
References 55 publications
(76 reference statements)
16
162
0
1
Order By: Relevance
“…Furthermore, the formation of droplets even in our simple model indicates that this might be quite a general phenomenon and that hydrophobic domains such as those seen in the molecular dynamics simulations of Khandelia et al [11] might be observed in a variety of systems.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Furthermore, the formation of droplets even in our simple model indicates that this might be quite a general phenomenon and that hydrophobic domains such as those seen in the molecular dynamics simulations of Khandelia et al [11] might be observed in a variety of systems.…”
Section: Discussionmentioning
confidence: 55%
“…We could also study how likely the droplet is to split off from the bilayer, for example by comparing the free energies of the bilayerencapsulated droplet and a system of a droplet covered by a monolayer in coexistence with a bilayer. Finally, droplets formed from a second species of amphiphile could be studied, to bring our calculations closer to the problem of lipid domains in bilayers [11,16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current model of LD biogenesis speculates that LDs are derived from the endoplasmic reticulum (ER) by a process that begins with the accumulation of neutral lipids between the leafl ets of phospholipid bilayers ( 3,19 ). Many studies have attempted to unravel how LDs form and grow, but this hypothesis still lacks direct evidence and the molecular mechanism Abstract Storage of cellular triacylglycerols (TAGs) in lipid droplets (LDs) has been linked to the progression of many metabolic diseases in humans, and to the development of biofuels from plants and microorganisms.…”
mentioning
confidence: 99%
“…Because lumenal acylCoA-dependent acylations do occur in the ER, such as ethanol esterification 13 and apoB palmitoylation, [14][15][16] some transporter/ channel-mediated process is likely to exist. To this effect, both N-ethylmaleimide-sensitive acyl-CoA acyltransferasemediated 17,18 and N-ethylmaleimide insensitive but mersalyl 20 Although a plethora of studies have dealt with the mechanism of cytosolic LD formation and composition, [21][22][23][24] information on the biosynthesis of lumenal LDs is limited in comparison. A number of factors potentially regulating formation of cytosolic LDs have been identified, including perilipins 25 and fat storage-inducing transmembrane proteins.…”
Section: Synthesis Of Tg On the Ermentioning
confidence: 99%